Direct Coaptation of the Phrenic Nerve With the Posterior Division of the Lower Trunk to Restore Finger and Elbow Extension Function in Patients With Total Brachial Plexus Injuries. Issue 2 (4th September 2015) - Wang, Shu-feng; Li, Peng-cheng; Xue, Yun-hao; Zou, Ji-yao; Li, Wen-jun; Li, Yucheng
ABSTRACT: BACKGROUND: To overcome the mismatch in nerve sizes in phrenic nerve transfer to the radial nerve for elbow and finger extension reanimation for patients with total brachial plexus injuries (TBPI), a selective neurotization procedure was designed. OBJECTIVE: To investigate the long-term results of phrenic nerve transfer to the posterior division of the lower trunk with direct coaptation in restoring elbow and finger extension after TBPI. METHODS: Phrenic nerve was transferred to and directly coapted with the posterior division of the lower trunk in 27 patients with TBPI. Seven patients were <18 years old (adolescent group), and the remaining 20 patients ≥18 years (adult group). RESULTS: Postoperative mean follow-up period was 54 ± 9 months (range, 48-85 months). The motor function attained M3 or greater in 81.5% of patients for elbow extension and in 48% of patients for finger extension. The percentage of patients who regained M3 or greater muscle power of finger extension in the adolescent group and the adult group was 71.4%, and 40%, respectively. Meanwhile, 85.7% in the adolescent group and 80% in the adult group achieved M3 or greater muscle power of elbow extension. There were no significant differences between the 2 groups. The elbow extension and finger extension were synchronous contractions and did not become independent of respiratory effort. CONCLUSION: This procedure simultaneously and effectively restores the function of elbow and finger extension in patients after TBPI. However, the patients could not do elbow and finger extension separately.